Personal Branding Agus Harimurti Yudhoyono Melalui Media Sosial Youtube @AgusYudhoyono - DEDEN JAELANI (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2024)
Indonesia will hold presidential and parliamentary elections in 2024 at both national and regional levels. Agus Harimurti Yudhoyono is one of the presidential candidates in the 2024-2029 elections. In political years where this, as done by Agus Harimurti Yodhoyono, will have a significant influence on the support of the Indonesian people, personal branding is an important component in the success of the plan. The development of information technology and the use of social media as a tool for developing personal branding is currently impossible to resist. Agus Harimurti Yudhoyono uses YouTube, a social media platform, to develop personal branding to attract the interest of the younger generation. The purpose of this research is to find out more about Agus Harimurti Yudhoyono's personal branding strategy on YouTube. By using foundations such as personal branding, agenda setting, framing and dramaturgy. The author uses qualitative research techniques. Framing analysis will be replaced by research that focuses on issues related to Agus Harimurti Yudhoyono's personal branding. Based on the findings of this study, personal branding, framing, and dramaturgy produce personal branding developed by Agus Harimurti Yudhoyono's management through YouTube social media which has formed a realistic personal branding. As a result, Agus Harimurti Yudhoyono's personal branding has become realistic.